(untitled) (Applied Biological Research, 2020)
Aquaporin 1 (AQP1) is a water channel protein located on the cell membranes of several epithelial and endothelial cells, and also significantly in tumor endothelia. Though the role of AQP1 in tumor progression has been substantiated sufficiently in past, very few studies have evaluated its immuno-histochemical expression in salivary gland tumors. The current study comparatively evaluated the AQP1 expression in both benign and malignant salivary gland tumors in human. The study included a total of 26 cases, 13 cases each from benign and malignant categories. The benign tumors included were pleomorphic adenoma (12), myoepithelioma (1) while malignant tumors included mucoepidermoid carcinoma (11), adenoid cystic carcinoma (1) and adenocarcinoma (1). The study demonstrated that AQP1 was immunolocalized to the non-luminal ductal cells in pleomorphic adenoma and adenoid cystic carcinoma. The intermediate and epidermoid cells of muco-epidermoid carcinoma showed a weak expression. Negative expression was noticed in myo-epithelioma and adenocarcinoma. The results showed no significant difference in the expression of AQP1 between benign and malignant salivary gland tumors; however, it hypothesized that AQP1 is significantly expressed by either myoepithelial cells or basal cells considering that the non-luminal region usually comprises these cells in a normal salivary gland.